Economic outcomes associated with deep surgical site infection from lower limb fractures following major trauma. (9th May 2022) - Png, May Ee; Petrou, Stavros; Knight, Ruth; Masters, James; Achten, Juul; Costa, Matthew L.
Abstract : Aims: This study aims to estimate economic outcomes associated with 30-day deep surgical site infection (SSI) from closed surgical wounds in patients with lower limb fractures following major trauma. Methods: Data from the Wound Healing in Surgery for Trauma (WHiST) trial, which collected outcomes from 1, 547 adult participants using self-completed questionnaires over a six-month period following major trauma, was used as the basis of this empirical investigation. Associations between deep SSI and NHS and personal social services (PSS) costs (£, 2017 to 2018 prices), and between deep SSI and quality-adjusted life years (QALYs), were estimated using descriptive and multivariable analyses. Sensitivity analyses assessed the impact of uncertainty surrounding components of the economic analyses. Results: Compared to participants without deep SSI, those with deep SSI had higher mean adjusted total NHS and PSS costs (adjusted mean difference £1, 577 (95% confidence interval (CI) -951 to 4, 105); p = 0.222), and lower mean adjusted QALYs (adjusted mean difference -0.015 (95% CI -0.032 to 0.002); p = 0.092) over six months post-injury, but this difference was not statistically significant. The results were robust to the sensitivity analyses performed. Conclusion: This study found worse economic outcomes during the first six months post-injury in participants who experience deep SSI following orthopaedic surgery for major trauma to the lower limb. However, the increase in cost associated with deep SSI was less than previously reported in the orthopaedic trauma literature. Cite this article: Bone Jt Open 2022;3(5):398–403.